Eksplorasi Tuturan dan Dinamika Bahasa Remaja di Dunia Game Online: Perspektif Psikolinguistik - Ninah Hasanah; Eldi Mulyana; Husna Epril Qinantri (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2025)
This study explores adolescents' speech and language dynamics in the context of online gaming from a psycholinguistic perspective. Linguistic variation in this digital space is viewed as a unique reflection of cognitive processes, language production, and social affiliations. The primary objective is to analyze how adolescents construct, process, and use non-standard language, slang, and code-switching and code-mixing patterns for effective communication and the construction of group identity in a fast-paced gaming environment. The case study method used was a descriptive qualitative approach. Data were obtained from participant observation of game interactions and in-depth interviews with adolescent participants (aged 15–20 years). Data were transcribed and analyzed using a social psycholinguistic framework, focusing on aspects of language production and comprehension (language processing), as well as lexical variation. The results show that adolescent speech is dominated by extreme lexical creativity, including novel slang, acronyms, and game-specific lexis. This phenomenon serves as a marker of cognitive processing speed and social boundaries. Code-switching and code-mixing patterns, especially between Indonesian and English, frequently occur for time efficiency and emotional expression. Psycholinguistic, these dynamics reflect high linguistic flexibility and rapid cognitive adaptation to real-time communication. The study concludes that the online gaming world plays a vital role as a language incubation arena, providing in-depth insights into the mechanisms of adolescent language adaptation in the evolution of digital communication.